Trim37-deficient mice recapitulate several features of the multi-organ disorder Mulibrey nanism - Kettunen, Kaisa M. (Biol Open, 2016)
Mulibrey nanism (MUL) is a rare autosomal recessive multi-organ disorder characterized by severe prenatal-onset growth failure, infertility, cardiopathy, risk for tumors, fatty liver, and type 2 diabetes. MUL is caused by loss-of-function mutations in TRIM37, which encodes an E3 ubiquitin ligase belonging to the tripartite motif (TRIM) protein family and having both peroxisomal and nuclear localization. We describe a congenic Trim37 knock-out mouse (Trim37(−/−)) model for MUL. Trim37(−/−) mice were viable and had normal weight development until approximately 12 months of age, after which they started to manifest increasing problems in wellbeing and weight loss. Assessment of skeletal parameters with computer tomography revealed significantly smaller skull size, but no difference in the lengths of long bones in Trim37(−/−) mice as compared with wild-type. Both male and female Trim37(−/−) mice were infertile, the gonads showing germ cell aplasia, hilus and Leydig cell hyperplasia and accumulation of lipids in and around Leydig cells. Male Trim37(−/−) mice had elevated levels of follicle-stimulating and luteinizing hormones, but maintained normal levels of testosterone. Six-month-old Trim37(−/−) mice had elevated fasting blood glucose and low fasting serum insulin levels. At 1.5 years Trim37(−/−) mice showed non-compaction cardiomyopathy, hepatomegaly, fatty liver and various tumors. The amount and morphology of liver peroxisomes seemed normal in Trim37(−/−) mice. The most consistently seen phenotypes in Trim37(−/−) mice were infertility and the associated hormonal findings, whereas there was more variability in the other phenotypes observed. Trim37(−/−) mice recapitulate several features of the human MUL disease and thus provide a good model to study disease pathogenesis related to TRIM37 deficiency, including infertility, non-alcoholic fatty liver disease, cardiomyopathy and tumorigenesis.